Hacks. Season three [videorecording (DVD)]. - Aniello, Lucia; Downs, Paul W.; Statsky, Jen, 1985-
Veteran standup Deborah Vance (Jean Smart) was worriedly watching the Vegas crowds shrink-and her casino bookings getting cut back accordingly. Millennial comedy writer Ava Daniels (Hannah Einbinder) was feeling the cancellation blowback from an ill-considered tweet. The reluctant pact for mutual professional survival and the generational friction that follows fuels this engaging HBO Max dramedy.